Probing the open state of cytochrome P450cam with ruthenium-linker substrates - Dunn, Alexander R. (The National Academy of Sciences, 2001)
Cytochromes P450 play key roles in drug metabolism and disease by oxidizing a wide variety of natural and xenobiotic compounds. High-resolution crystal structures of P450cam bound to ruthenium sensitizer-linked substrates reveal an open conformation of the enzyme that allows substrates to access the active center via a 22-Å deep channel. Interactions of alkyl and fluorinated biphenyl linkers with the channel demonstrate the importance of exploiting protein dynamics for specific inhibitor design. Large changes in peripheral enzyme structure (F and G helices) couple to conformational changes in active center residues (I helix) implicated in proton pumping and dioxygen activation. Common conformational states among P450cam and homologous enzymes indicate that static and dynamic variability in the F/G helix region allows the 54 human P450s to oxidize thousands of substrates.